Developing an Effective Roadmap to Emissions Reduction in the Energy Sector: Strategies, Challenges, and Opportunities - Provodnikova, Anna; Bouadjel, Aissam (Global journal of Business and Integral Security, 2026)
Emissions control frameworks in the fossil fuel process plants often fail to deliver meaningful environmental outcomes due to a combination of technical, organizational, and geopolitical factors. Many initiatives remain reactive, driven by short-term compliance rather than integrated into long-term sustainability strategies. Weak regulatory enforcement, lack of leadership commitment, and absence of clear roadmaps result in fragmented implementation and poor accountability. Political conflicts, market volatility, and shifting energy priorities further disrupt continuity, forcing companies to prioritize production and energy security over emissions reduction. Environmental risks are frequently undervalued in corporate risk assessments, treated as external or reputational concerns rather than core operational threats. Additionally, slow advancement and limited adoption of technologies such as vapor recovery systems, carbon capture, and emissions reuse hinder progress. Overcoming these failures requires strong leadership, risk-based planning, and strategic alignment between regulators, operators, and technology providers to achieve sustainable and measurable emissions control.